2016
DOI: 10.1016/j.juro.2015.12.080
|View full text |Cite|
|
Sign up to set email alerts
|

Examining Penile Sensitivity in Neonatally Circumcised and Intact Men Using Quantitative Sensory Testing

Abstract: Findings suggest that minimal long-term implications for penile sensitivity exist as a result of the surgical excision of the foreskin during neonatal circumcision. Additionally, this study challenges past research suggesting that the foreskin is the most sensitive part of the adult penis. Future research should consider the direct link between penile sensitivity and the perception of pleasure/sensation. Results are relevant to policy makers, parents of male children and the general public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 22 publications
1
57
0
1
Order By: Relevance
“…Some large nationally representative cross-sectional surveys24, 25 have included countries with high and low male circumcision rates, controlling for demographic factors that might influence attitudes toward circumcision. Several studies have compared intravaginal ejaculatory latency time11, 24, 25, 26, 27, 28 and a few small studies have reported direct physiologic measurements of penile sensitivity and sexual response27, 29, 30, 31 in circumcised and uncircumcised men, finding no evidence for detrimental physiologic effects of male circumcision. Two cohort studies using data from RCTs12, 13 in Africa offer the best evidence to date on the effects of VMMC on male sexual function and satisfaction, suggesting no significant impairments in sexual function or satisfaction and some improvements in sexual function after male circumcision.…”
Section: Discussionmentioning
confidence: 99%
“…Some large nationally representative cross-sectional surveys24, 25 have included countries with high and low male circumcision rates, controlling for demographic factors that might influence attitudes toward circumcision. Several studies have compared intravaginal ejaculatory latency time11, 24, 25, 26, 27, 28 and a few small studies have reported direct physiologic measurements of penile sensitivity and sexual response27, 29, 30, 31 in circumcised and uncircumcised men, finding no evidence for detrimental physiologic effects of male circumcision. Two cohort studies using data from RCTs12, 13 in Africa offer the best evidence to date on the effects of VMMC on male sexual function and satisfaction, suggesting no significant impairments in sexual function or satisfaction and some improvements in sexual function after male circumcision.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study across all sensation types (touch, warmth and pain) by Canadian researchers, Bossio et al [70] concluded that, "the foreskin is not the most sensitive part of the penis". Although the foreskin was sensitive to fine-touch, in referring to Sorrells et al [68], Bossio et al stated that their study, "challenges past research suggesting that the foreskin is the most sensitive part of the adult penis" [70].…”
Section: Denialismmentioning
confidence: 99%
“…British pediatricians now tend to dismiss routine infant circumcision, American physicians keep on advocating it quite generally [47][48][49]. Nowadays, most clinicians would not remove an appendix or the tonsils prophylactically.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Interestingly, although by circumcision corpuscular receptors of touch are removed, a recent sensory testing study found no long-term implications for penile sensitivity in circumcised males and even challenges the image of the foreskin to be the most sensitive part of the penis [48]. It is rather that, due to circumcision, loss of sensitivity of the glans as a result of keratinization will handicap ejaculation.…”
Section: Clinical Aspectsmentioning
confidence: 99%